Studi Eksperimental Beton Mutu Tinggi Dengan Agregat Batok Kelapa Dan Terak Baja - Anisa Tikupadang; Herman Parung; Benny Kusuma (Paulus Civil Engineering Journal, 2021)
Steel slag is a waste from the steel smelting industry. Along with the increasing demand for steel, it can also cause steel waste to increase. Coconut shell is a solid waste from the rest of coconut processing. This study aims to obtain the compressive strength, split tensile strength, flexural strength, and modulus of elasticity with coarse aggregate substituted for steel slag and coconut shell, with a concrete quality of f'c 45 MPa. The results of this study that the compressive strength of concrete obtained, 100% crushed stone aggregate increased 5.213% and coconut shell substitution and steel slag increased 1.650%. The value of the split tensile strength of concrete, 100% crushed stone is 9.312% and the substitution of coconut shells and steel slag is 9.073 of the compressive strength. The value of flexural strength, 100% crushed stone is 0.827√(f'c) and the substitution of coconut shell and steel slag is 0.752 f'c from the compressive strength. The modulus of elasticity of concrete, 100% crushed stone is 24845,351 MPa and substitution of coconut shells and steel slag is 20674,005 MPa.